La gestión de inventarios en las pymes del sector de la construcción. - Romero Agila, Silvana Estefania; Saenz Encalada, Selena Solange (My University, 2021)
Inventory management is a tool that helps companies to manage and control their products correctly by establishing clear policies, methods and procedures. The objective of the research was to determine an inventory management model for the efficient management of materials of SMEs oriented to the construction sector, where a quantitative and qualitative approach was used, the study population were Pymes related to the construction sector within the province of El Oro; selecting through the application of a non-probabilistic purposive sampling, 42 Pymes. The information was processed using the statistical program IBM SPSS 21, having as results that many companies manage their inventories using Excel and even do it manually; the implementation of a software would help to automate and unite processes and information, for this they should acquire more knowledge and new tools for better control that will allow a reduction in time and costs that can be generated by carrying out this process empirically. The proposal for the elaboration of a process diagram is established, representing a deterministic model that helps to carry out a process in an orderly and detailed manner with established policies that allow a periodic review of inventories for constant improvement.
La gestión de inventario es una herramienta que ayuda a las empresas a administrar y controlar sus productos correctamente estableciendo de forma clara políticas, métodos y procedimientos. El objetivo de la investigación fue determinar un modelo de gestión de inventarios para el manejo eficiente de los materiales de las Pymes orientadas al sector de la construcción, donde se empleó un enfoque cuantitativo y cualitativo, la población objeto de estudio fueron las pymes relacionadas al sector de la construcción dentro de la provincia de El Oro; seleccionando mediante la aplicación de un muestreo no probabilístico intencional, 42 pymes. La información se procesó mediante el programa estadístico IBM SPSS 21, teniendo como resultados que muchas empresas administran sus inventarios utilizando Excel e incluso lo realizan de forma manual; la implementación de un software ayudaría a automatizar y unir procesos e información, para ello deben adquirir más conocimientos y nuevas herramientas para un mejor control que permitirá una reducción en tiempos y costos que se puedan generar al llevar este proceso empíricamente. Se establece la propuesta de elaboración de un diagrama de procesos, representando un modelo determinístico que ayude a llevar un proceso de forma ordenada y detallada con políticas establecidas que permitan efectuar una revisión periódica de inventarios para un mejoramiento constante.
Keywords: INVENTARIOS; CONTROL; GESTIÓN